Post-Crisis Changes in Banking and Corporate Landscapes The Case of Thailand - Molnar, Margit (OECD Publishing, 2003)
This study investigates the relative importance of factors shaping banking and corporate landscapes in Thailand after 1997 through an empirical analysis of micro-data of Thai banks and firms. The results of the analysis of the bank data show that the deceleration of bank credit growth is mainly attributable to the fallout from the Asian crisis and postcrisis regulatory changes. While high non-performing loans (NPLs) and foreclosed assets on balance sheets hinder the resumption of lending, those banks that were well capitalised, larger or domestic could resume lending faster. The analysis also showed that big, domestic, well-capitalised banks with higher NPLs are more prone to diversify into securities investments. The analysis of the firm sample indicates that Thai firms have diversified their sources of financing over the period of 1997-2000, which is reflected in the rise of the share of debt securities and trade financing. As a conclusion from the above analyses, the ...
Keywords: Economics; Thailand